Effect of Delaying Urine at Room Temperature and Cold Temperature on the Number of Bacteria in Urinary Tract Infection Patients - Rini, Chylen Setiyo (Jurnal Analis Kesehatan Kendari, 2024)
Urinary Tract Infection is an infection of the urinary tract, especially the kidneys, bladder, ureters and urethra which causes various microorganisms, generally bacteria. If urine is left for too long it will affect the validity of the examination results in supporting the diagnosis of an examination, especially UTI. The aim of this study was to determine the effect of delaying urine at room temperature and cold temperature on the number of bacteria in Urinary Tract Infection patients. The method used was Laboratory Experimental with Accidental Sampling sampling techniques in accordance with the inclusion criteria, totaling 5 samples. The results of the study at room temperature (20-25°C) (12.9 /ml). The data were analyzed statistically using the Friedman test, showing a significance value of P<0.05, namely 0.003, that there was an effect of delaying urine at room temperature and at cold temperatures on the number of bacteria in sufferers of Urinary Tract Infections (UTI).